Revisiting Korean Kaein changgu nori: Rhythm Writ Large - Keith Howard (Analytical Approaches to World Music, 2025)
Rhythm is central to Korean music and is most developed in pieces for the Korean changgu, an hourglass-shaped double-headed drum. This paper revisits a danced piece for solo drum, Kaein changgu nori, created by Kim Pyŏngsŏp (1921–1987), and my own experience of learning and performing it. Kaein changgu nori is a 15-minute piece of around 260 units (karak) sequenced together through motivic development in five sections (or movements) each based on a foundational archetype model (changdan). Kim’s piece attracted much attention from both Koreans and foreign scholars and students in the 1970s and 1980s, and it continues to have a dedicated preservation society. Old and new performances and workshopped classes of it proliferate online. However, although thoroughly grounded in the percussion bands of the North Chŏlla region, Kim was considered by some to have moved too far from “tradition,” leaving his piece and its practitioners outside the well-established South Korean intangible heritage preservation system. In retrospect, his piece can be considered to mark a transition from the music of rural percussion bands (nongak/p’ungmul) of old to a repertoire more suited to today’s urban stages. Its importance is that it changed the rhythmic grammar of drumming, replacing the static models and surface improvisation of bands of old with the linear development of motifs which move away from and back to an archetype model. However, Kims was never a completely fixed piece; adjusted and recomposed elements during performances and in his teaching. In revisiting it, I analyse its rhythmic grammar, turning on its head the evolutionary theory that holds melody and harmony as more significant than rhythm. I outline its development and discuss the people who have connected through it, documenting its reinterpretation in recent years. The article includes a full notation, based on Kim’s performance and teaching in autumn 1985.